Determination of carbohydrate amounts of various cheese species presented to sale in the market - CEBECİ, AYBİKE; YALÇIN, BAHATTİN; GÜNEŞ, FATMA ESRA (My University, 2018)
The aim of this study is to determine the amounts of lactose, glucose, galactose, starch and total carbohydrates in cheese types presented to sale in the market. In the study, from different points of sale in Istanbul province 15 different types of cheese were investigated. Carbohydrate amounts of the cheeses examined were determined in two ways as theoretically (by difference method) and analytically (by HPLC). The amount of analytically determined carbohydrate of white cheese types was lower than the theoretically calculated amount (P<0.05). However, there was no statistically significant difference between the theoretical and analytically calculated carbohydrate amounts of kashar and other cheese types (P>0.05). In addition, it was determined that the amount of carbohydrates of ripened cheeses was lower than carbohydrate amounts in fresh cheeses. Consequently, analytical calculation of carbohydrate amount gives more accurate results. This should be taken into account when evaluating the macronutrient content of cheese.
Keywords: cheese; carbohydrate; lactose; galactose; glucose